Frequency Stability Control Strategy for Large-scale Grid Connections with DFIG Units - Lei YANG; Zhichao WANG; Xin ZHOU; Shengnan LI; Peng HE; Chuan XIANG; Jie ZHANG; Delin WANG (Zhongguo dianli)
The penetration rate of wind power in the power grid has been increasing year by year. A lot of contributions have been made to optimize the power supply structure, energy conservation and emission reduction, however, due to the natural fluctuation and uncertainty of wind speed, grid integration with large-scale wind power is bound to impact the frequency stability of the power grid. With regard to this problem, the doubly-fed induction generator (DFIG) control system was studied in this paper and then the primary frequency modulation control strategy following large-scale DFIG connection was established. On the basis of the existing droop control and virtual inertia control strategy, the droop control part is implemented by virtue of variable coefficient according to the input wind speed and the frequency fluctuation of grid side, as to improve the droop control characteristics. Additionally, the operating conditions of DFIG are classified, and the load reduction coefficient is used to reduce the curtailment of wind while the DFIG is running at limited power level. The effectiveness of the proposed primary frequency modulation control strategy is verified by means of the simulation of an actual power grid model with large-scale wind power grid connection.